2016
DOI: 10.1159/000449242
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hemodialysis on T Regulatory Cells: A Meta-Analysis and Systematic Review

Abstract: Aims: The study aimed to determine whether the available literature supports a positive or negative influence of dialysis on regulatory T-cells (Tregs). Methods: We performed a systematic search and a meta-analysis. Mean differences in Tregs number of chronic kidney disease stages G5 on dialysis patients (CKD G5D) and healthy controls (HCs) were compared. Random effects model was applied. The software used was general package for meta-analysis (version 4.3-0, depends R (≥2.9.1)). Results: Five studies were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The pooled 1 and 5 min Apgar scores, 7.94 and 8.97, respectively, were not significantly different from the normal range ( 7 10 ). As expected, the 1 and 5 min Apgar scores had significant positive relationships ( P = 0.04, P = 0.04, respectively) with birth weight.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The pooled 1 and 5 min Apgar scores, 7.94 and 8.97, respectively, were not significantly different from the normal range ( 7 10 ). As expected, the 1 and 5 min Apgar scores had significant positive relationships ( P = 0.04, P = 0.04, respectively) with birth weight.…”
Section: Discussionmentioning
confidence: 61%
“…The meta-analysis included all studies. Pooled means on age, gestational age, blood assay values, antibody levels, and pooled prevalence on preterm birth, C-section delivery, vertical transmission, abnormal blood assay values, and elevated antibody levels were assessed using the Generalized Linear Mixed model; the meta-analysis was performed using the “meta” ( 10 ) and “metaprop” ( 11 ) packages in the R statistical software ( 12 ). The random effects model was applied to calculate the pooled prevalence and single means with a 95% confidence interval (95% CI).…”
Section: Methodsmentioning
confidence: 99%
“…We studied the expression of these molecules over a period spanning from before transplantation up to one year after transplantation, and we observed that pre-transplant levels of CTLA-4 and FOXP3 were significantly reduced compared to healthy subjects. Accordingly, recent studies and a meta-analysis have suggested that end-stage renal disease (ESRD) and RRT influence immunity by lowering CD4 + lymphocytes and Tregs (25)(26). After transplantation, we documented a robust decrease in both CTLA-4 and FOXP3 expression compared to baseline levels, probably due a combined effect of immunosuppressive treatment and immune response.…”
Section: Association Between Atcmr Onset and Clinical Or Molecular Vasupporting
confidence: 47%
“…Peripheral venous blood (3 ml) was drawn directly into Tempus Blood RNA tubes (Thermo Fisher Scientific Inc., Waltham, MA-US), according to the manufacturer's protocol, frozen and stored at -20°C until processing. Whole blood total RNA was extracted using a Tempus Spin RNA isolation (Thermo Fisher Scientific Inc.), which uses an RNA isolation method (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) aTCMR-free vs. aTCMR-positive patients) was normalized with the 2 -∆CT logarithm 10 (log2 -∆CT ) compared to the endogenous control, to correct the asymmetric distribution of the data.…”
Section: Rna Isolation and Gene Expression Analysismentioning
confidence: 99%
“…With regard to Tregs, the influence of dialysis on their counts and function remains to be further clarified ( 43 45 ). Thus, a recent meta-analysis showed that ESKD patients not undergoing dialysis displayed a lower percentage of Tregs on CD4+ T-cells compared to healthy individuals, but on the other hand no significant difference was observed with respect to Tregs percentage between hemodialysis patients and healthy individuals ( 44 ). We found no significant differences between the percentage of Tregs on total lymphocytes and normal controls.…”
Section: Discussionmentioning
confidence: 99%